2019
DOI: 10.3390/cancers11060850
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of TRAIL Signaling: Implication for Cancer Therapy

Abstract: One of the main characteristics of carcinogenesis relies on genetic alterations in DNA and epigenetic changes in histone and non-histone proteins. At the chromatin level, gene expression is tightly controlled by DNA methyl transferases, histone acetyltransferases (HATs), histone deacetylases (HDACs), and acetyl-binding proteins. In particular, the expression level and function of several tumor suppressor genes, or oncogenes such as c-Myc, p53 or TRAIL, have been found to be regulated by acetylation. For exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 230 publications
(291 reference statements)
0
27
0
Order By: Relevance
“…Many researches have reported that HDACi can induce G1 phase arrest with reduction of c-Myc and induction of p21 [30,[36][37][38]. It is clear that c-Myc expression levels tightly relate to cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Many researches have reported that HDACi can induce G1 phase arrest with reduction of c-Myc and induction of p21 [30,[36][37][38]. It is clear that c-Myc expression levels tightly relate to cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…While tumor necrosis factor-related apoptosis inducing ligand (TRAIL) selectively induces apoptosis of tumor cells [ 9 , 11 , 49 , 50 ], approximately 20% of them develop resistance to TRAIL, limiting its potential use in clinic [ 22 , 49 , 51 ]. Surprisingly, cancer cells’ refractory to conventional chemotherapy, sometimes displays high sensitivity to TRAIL-induced cell death [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…c-myc is not only linked to survival, proliferation, and angiogenesis but is also involved in epigenetic control of EMT. Recent reports document a close cross-communication between c-myc and HDAC [82,83], which is highly relevant from a clinical viewpoint. Nearly 90% of all cancers are thought to be caused by epigenetic modification [84], whereby elevated expression of HDACs correlate with a poor prognosis [85].…”
Section: Curcumin Plus Bacillus Calmette-guerin (Bcg) Intravesical Therapymentioning
confidence: 97%
“…Kamat et al [81] did not investigate the HDAC expression level and histone acetylation in their study. However, up-regulation of tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) receptors under curcumin treatment and BCG might be traced back to a c-myc-HDAC interaction [83]. Since curcumin has been identified as a natural HDAC-inhibitor, it may therefore carry high potential in supporting a BCG-based regimen.…”
Section: Curcumin Plus Bacillus Calmette-guerin (Bcg) Intravesical Therapymentioning
confidence: 99%